ترکی میں احیائے اسلام کی تحریکیں: ایک مطالعہ: A Study of Islamic Revival Movements in Turkey - Dr. Zakra Perveen (Al-Qamar, 2018)
A number of protestant Islamic movements had been prompting in various eras of the history of Islam. Several religious and ameliorative movements started specifically in Iran, Egypt, Syria, Lebanon, North Africa, Afghanistan, Turkey and India during the midst of thirteenth century A.H. These movements arose after centuries of passivity. They were, to some extent contrary to the political, economic, cultural and colonial policies of West while in the Islamic world considered as efforts of Islamic reforms and re-advancement of Ummah. Many of these movements also provoked in Turkey for the establishment of Islamic ideology. Some of them are as under: "Pan Islamism" movement of Syed Jamal-u- Din Afghani Movement against inspiration of West Struggle of Midhat Pasha and Mustafa Fazil Pasha. Struggle of Islamists Milli-gorush movement and Najm-u- Din Arbakaan Islamization of Recep Tayyip Erdogan.